ENGLISH LANGUAGE ACQUISITION CHALLENGES AMONG INDONESIAN TRAVEL AGENTS IN MEDAN: A QUALITATIVE STUDY OF PROFESSIONAL COMMUNICATION WITH INTERNATIONAL CLIENTS - Tri Utami; Alemina Br. Perangin-angin (Jurnal Suluh Pendidikan, 2026)
This study investigates the challenges of English language acquisition among Indonesian travel agents in their professional communication with international clients. Despite the growing demand for English competence in tourism, little research has examined how linguistic, affective, and contextual factors influence workplace communication in this sector. Addressing this gap, the study aims to identify specific language barriers, coping strategies, and training needs within the framework of Second Language Acquisition (SLA) and English for Specific Purposes (ESP). A qualitative exploratory design was employed involving ten travel agents from registered agencies in Medan, North Sumatra. Data were collected through open-ended written questionnaires and were analyzed thematically following Braun and Clarke’s procedure. The analysis yielded four main themes: limited vocabulary and pronunciation, grammatical and listening comprehension difficulties, affective barriers such as anxiety and low confidence, and coping strategies alongside the need for ESP-based training. The findings reveal that English proficiency among travel agents is shaped by limited authentic exposure, insufficient output opportunities, and emotional factors that restrict communication confidence. The study highlights the necessity of contextualized ESP instruction integrating workplace simulations, pronunciation training, and confidence-building activities. These results contribute to SLA and ESP theory by emphasizing the interdependence of linguistic, affective, and contextual dimensions in professional language learning, while providing practical implications for tourism educators and industry stakeholders in designing effective English training programs.